Hyperacusis in children: A review - Elena A. Levina; Sergey V. Levin; Alexey V. Khramov; Serafima B. Sugarova; Viсtor A. Voronov (Consilium Medicum, 2022)
The problem of hyperacusis a condition in which sensitivity to sounds is increased is common in world practice. According to the ICD classification of diseases of the World Health Organization (WHO), the concept of hyperacusia is used as a general term for abnormal auditory sensations, (ICD code H93.2). Up to 17% of children and adolescents are disturbed by unpleasant sensations in the sounds of the environment. In this review, we would like to analyze the current state of the issue, to understand the terminology of similar conditions. To study the nature of complaints, varieties and causes of this condition, the relationship with concomitant diseases. Designate diagnostic principles, algorithms for managing patients with hyperacusis by different specialists. Consider the options for the treatment and rehabilitation of children and adolescents suffering from hyperacusis proposed in world practice.